Providing hotel incentives to increase employee loyalty - Ni Made Visca Febrianti; I Gusti Agung Mas Krisna Komala Sari; Ni Nyoman Triyuni; I Ketut Suarta (Politeknik Negeri Bali, 2019)
The background of this research was based on of importance of providing incentives to employees at 4-star hotel in Seminyak, Bali. The purpose of this research to determine whether the provision of incentives can increase employee loyalty at the hotel. The data was collect by interviews, observation and documentation, incentive variable and employee loyalty is by using questionnaire and percentage. The data source were used primer and secondary data. The data will analyzed used qualitative descriptive and quantitative descriptive. This research of this study indicate that the providing of incentives by the hotel able to improve employee loyalty. This is indicated from the results of questionnaire as many as 85,2% answered strongly agree and agree, while 14,8% answered disagree. The suggestion in this study is that giving incentives to the hotel is good, but it need to increase the nominal amount of incentives provided so as to increase employee loyalty. Employee need to increase loyalty of that work so that hotel revenue will be increase, and incentives are also increased.